Grupos de isometrias e aspectos culturais - RAMOS, Augusto Cezar Abreu (2023)
This work intends to develop the study of isometries and use Group Theory as a tool to investigate the incidence of symmetry patterns in widely accessible cultural artifacts in the culture of the North region of Brazil. These artifacts are ceramics, tapestries and Other objects. One of the objectives of this investigation is to promote the cultural relevance of these patterns and the wealth of geometric properties contained in these artifacts. For this, a study will be made of the isometries of the Euclidean plane and its properties, showing that these can be taken as elements of some groups, in particular, groups of Rosacea and Friso. In this regard, we will prove the respective classification theorems, as well as auxiliary results. We concluded the work by recognizing the groups in pieces from the Verônica Tembé memorial and the Paracuri Handicraft Fair.